2021
DOI: 10.1186/s12889-021-10680-5
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of personal protective health behaviour against COVID-19

Abstract: Background Novel coronavirus disease 2019 (COVID-19) has become a pandemic, and over 80 million cases and over 1.8 million deaths were reported in 2020. This highly contagious virus is spread primarily via respiratory droplets from face-to-face contact and contaminated surfaces as well as potential aerosol spread. Over half of transmissions occur from presymptomatic and asymptomatic carriers. Although several vaccines are currently available for emergency use, there are uncertainties regarding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 28 publications
1
58
0
2
Order By: Relevance
“…Handwashing and covid-19 incidence —Three studies with a total of 292 people infected with SARS-CoV-2 and 10 345 participants were included in the analysis of the effect of handwashing on incidence of covid-19 366368. Overall pooled analysis suggested an estimated 53% non-statistically significant reduction in covid-19 incidence (relative risk 0.47, 95% confidence interval 0.19 to 1.12, I 2 =12%) (fig 3).…”
Section: Resultsmentioning
confidence: 99%
“…Handwashing and covid-19 incidence —Three studies with a total of 292 people infected with SARS-CoV-2 and 10 345 participants were included in the analysis of the effect of handwashing on incidence of covid-19 366368. Overall pooled analysis suggested an estimated 53% non-statistically significant reduction in covid-19 incidence (relative risk 0.47, 95% confidence interval 0.19 to 1.12, I 2 =12%) (fig 3).…”
Section: Resultsmentioning
confidence: 99%
“…Frequent handwashing after outdoor activities and before touching the mouth/nose area reduced the risk of infection by 97.9 and 69.7%, respectively ( 16 ). According to a survey by Watanabe and Yoshikawa ( 17 ), the number of children with infectious diseases (e.g., influenza or pneumonia) has reduced by half.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported the effectiveness of non-vaccine public health measures and personal health protection behaviors in preventing COVID-19 [ 16 , 17 , 18 , 19 ]. A systematic review and meta-analysis reported RRs of COVID-19 infection for handwashing, mask-wearing, and physical distancing of 0.47 (95% CI: 0.19–1.12), 0.47 (95% CI: 0.29–0.75), and 0.75 (95% CI: 0.59–0.95), respectively [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Non-pharmaceutical public health measures other than vaccines and personal health prevention behaviors reportedly prevent COVID-19 [ 16 , 17 , 18 ]. A meta-analysis revealed that the incidence of COVID-19 is negatively associated with handwashing (relative risk [RR]: 0.47, 95% CI: 0.19–1.12), mask-wearing (RR: 0.47, 95% CI: 0.29–0.75), and physical distancing (RR: 0.75, 95% CI: 0.59–0.95) [ 17 ].…”
Section: Introductionmentioning
confidence: 99%